Reversible pulpitis accompanied with sinus tract on buccal side of the right maxillary first premolar teeth: case report - Andi Sumidarti; Sitty NM. Moersidi (Journal of Dentomaxillofacial Science, 2019)
Objective: Reversible pulpitis can occur in superficial and medium caries, with symptom of sensitivity in a cold drink, sweetness, air, or mechanical contacts on exposed dentine. Subjective, objective and adjunctive examination of radiographic of the tooth 14 showed that there was caries in the proximal section.Methods: The patient was then followed up to observe the sinus tract in the buccal section as well as to know the patient's perceived complaints after the restoration. After removal of the caries tissue on the proximal tooth of 14, then restoration was made and followed up in the first and fourth weeks, the sinus tract in the buccal region was closed, and the sensitivity of the tooth regresses 14 to 16 was lost.Results: The symptom disappears in a short time but was felt long ago or during a long period of time. Mostly sinus tract found in the oral mucosa as the results from pulp or periapical tissue damage. Sinus tract is formed as a result of the discharge of the pus through bone or soft tissue and is formed in the oral mucosa. Sinus tract not always come from pulp or periapical disorders, but also from periodontal disease.Conclusion: A study has been conducted on a patient with dental caries and sensitive in the teeth 14 to 16. The 14th tooth wasdiagnosed as reversible pulpitis and there was sinus tract on the buccal side.